Doxofylline for Pediatric Asthma Steps 1–4. Pediatric Asthma: New Role for an Old Drug - Fierro, Vincenzo; Piscitelli, Anna Lucia; Battaglia, Edda; Fiocchi, Alessandro (Frontiers in Pediatrics, 2022)
The panoply of anti-asthma drugs for children between 6 and 18 years is not limited to those reported in the guidelines. In this review, we will re-assess the role of doxofylline, a xanthine characterized by a much higher handling than that of theophylline, as add-on treatment in paediatric asthma grade 1 – 4. Ten studies evaluated doxofylline in the treatment of asthma of patients non-responsive to the first-line inhaled corticosteroids. Of these, two included children and one was exclusively paediatric. According to their results, doxofylline exerts a powerful bronchodilator and anti- inflammatory activity, which can be exploited when the inhaled oral corticosteroids are not sufficient to get the desired effect of reducing symptoms. Unlike theophylline, doxofylline does not require blood testing. It can be administered together with or as an alternative to a series of other drugs considered in additional therapy. In particular, doxofylline could be preferable in the following conditions: risk of low compliance with inhalers; risk of neurologic side-effects with LTRA; risk of serious asthma-related events attributable to LABAs; risk of discontinuation due to perceived inefficacy with ICS/LABA; doubts on the efficacy of LAMA; need for concomitant use of drugs that interfere with cytochrome p450, as some antibiotics, anti-epileptics, and antiarrhythmics.